Flora cormofită din aria naturală protejată Fâneţele seculare Ponoare-Bosanci (Suceava) [The cormophyte flora in natural protected area “Fâneţele seculare Ponoare-Bosanci” (Suceava)] - Cezar Tomescu; Andreea Găitan (Bucovina Forestieră, 2014)
. One of the most important floristic reserves, ”Fâneţele seculare Ponoare-Bosanci” is located in north-western Romania, in Suceava County, at 9 km south of Suceava City. The vegetal richness of Ponoare-Bosanci reserve was studied during the time by many biologists, who identified numerous species of cormophyte, belonging to very different habitats or regions. In the last 30-40 years, the floristic studies in this area were fewest. The contribution of this research is to update the floristic data (the vascular plant diversity) of Ponoare-Bosanci reserve and to analyze the temporal evolution of flora, compared with previously recorded data. We identified 609 of vascular plants and we analysed their taxonomy, life form categories, floristic elements, average of ecological indices and the so zological categories. 508 of the species identified by different authors, were identified in the field by the current study, but 44 species have not been found. Also, we have identified 33 new native vascular plant species and 24 cultivated species in the reserve area. All these species are included into 72 families and 298 genera. Regarding bioforms, hemicryptophytes has the highest proportion (51,48%), followed mainly by therophytes (15,94%), geophytes (11,03%), phanerophytes (9,63%) and hemitherophytes (8,93%). In terms of phytogeographic elements, the Eurasian has the highest percentage (48,84%), followed mainly by the European (11,72%), Central European (11,54%), Circumpolar (8,88%) and Pontic (8,56%). Average of ecological indices showed a large presence of full sun plants (L = 7.01), mesotherm plants (T = 5.73), meso-xerophyte plants (F = 5.17), neutrophil species (R = 7.08) and ologo-nitrophile species (N = 4.64).